Guidelines for genetic management in mammal translocation programs. (September 2019) - Pacioni, Carlo; Wayne, Adrian F.; Page, Manda
Abstract: Adequate levels of genetic diversity are important for the long-term success of translocated populations. Typically, population genetic theory and mathematical models are used to inform expected outcomes in different contexts. However, difficulties arise when trying to translate theoretical expectations into management actions. Providing practical guidelines on how to maximise the genetic diversity of translocated populations will help bridge this gap. In this study we develop guidelines for genetic management in translocation programs that consider genetic dynamics associated with population establishment, the harvest of founders from a source population, and the supplementation of an existing population over eight generations. Guidelines were informed by individual-based modelling. Given the nature of the modelling framework that we adopted, we report results in terms of the actual number of individuals and genetic diversity parameters as these are estimated in field-based studies. Our results demonstrate that 10 releases of 50 or two releases of 100 individuals should be carried out to establish a new population. Repeated harvests (each) of >30% of a source population within a generation had a negative impact on its genetic diversity and demographics. The survival of >20% of the supplemented individuals was needed for the supplementation program to be effective. Concurrently, the survival of resident animals also had a major effect. We make available a R utility to explore potential outcomes under different management scenarios. We considered our results to be directly applicable to polygamous, continuous breeder species, and generally informative for a wide range of vertebrate species.